PENGARUH MODEL PEMBELAJARAN KOOPERATIF TERHADAP HASIL BELAJAR KOGNITIF DITINJAU DARI KEMAMPUAN AKADEMIK MAHASISWA - Fahruddin -; A. Wahab Jufri; Jamaluddin - (Jurnal Penelitian Pendidikan IPA, 2016)
This research aims to determine the effect of cooperative learning on cognitive learning outcomes in terms of students' academic abilities. This study was aquasi-experimental research design with non-equivalent pretest-posttest control group design with 2x4 factorial design. The study population was a student of biology education STKIP Bima semester IV, total of 8 classes with a number of 336 students. Samples were obtained through a simple random sampling technique, of which there are 8 classes taken 4 classes as the sample with 168 students.The research instrument is a cognitive achievement test. The data were analyze dusing statistical techniques Anacova two paths. The results showed that 1) There is influence of cooperative learning model type STAD, Jigsaw II, and the TGT to the cognitive achievement of students (p <0.05), 2) There is influence of academic ability on the cognitive achievement of students (p <0.05) , 3) There is no influence to interaction effect between cooperative learning model type STAD, Jigsaw II, and TGT with academic ability of the student cognitive learning outcomes (p> 0.05), 4) Different test results show that the cooperative learning model TGT significant differences in their effects oncognitive learning outcomes, compared with Jigsaw II, and STAD (coefficient positively and sig. <0,05).